Analisis Penyebab Rendahnya Kreativitas dan Motivasi Belajar Matematika di SDN 04 Tegalgede Tahun 2015 - Hastuti, Lina Ayu; , Drs. Muhroji, S.E.,M.Pd (2016)
The purpose of this study is: Knowing the causes, the effects and how to cope with low creativity and motivation to learn mathematics in SDN 04 Tegalgede 2015. This type of research is the analysis of qualitative research design using case studies. Research conducted at SDN 04 Tegalgede Karanganyar and focused on class IV. Sources of data used are, teachers, 2 students and principals. Data collection techniques such as observation, interviews and documentation. The results showed there are two factors causing low creativity in learning mathematics, namely: 1) The teacher does not give students the opportunity to look for ways that they think is easier, and 2) Teachers do not use methods that can develop creativity. There are three factors causing low motivation to learn mathematics, namely: 1) Teachers do not use a variety of methods, 2) The lessons are very saturated, and 3) Teachers are not to associate the material with everyday life. The influence of the low creativity and motivation to learn math is the student scores to be low. Work done to improve mathematics learning creativity, there are two: 1) The props, and 2) Motivate. The work done to improve the motivation to learn math, there are three, namely: 1) Engage students in the assessment of homework, 2) peers, and 3) Meronce Flat Keywords: creativity, motivation, learning, mathematics